Retained stone retrieval basket causing chronic pancreatitis: a case report - Lee, James Wai Kit; Tan, Ming Yuan; Koh, Calvin; Iyer, Shridhar Ganpathi; Gao, Yujia (Frontiers in Surgery, 2023)
Background Endoscopic Retrograde Cholangiopancreatography (ERCP) is a common procedure performed for choledocholithiasis and gallstone pancreatitis. Though a relatively low risk procedure, it is not without its complications. Cases of impacted Dormia baskets during stone retrieval have been reported, but these are usually retrieved surgically during the same setting. Case Summary A 40-Year-Old Man presented to our hospital with an episode of epigastric pain and discomfort. He has a prior background of recurrent episodes of pancreatitis of which he underwent prior endoscopic therapy in his home country. Initial investigates revealed a metallic object seen on both the abdominal X-Ray, computer tomographic scan of the abdomen and pelvis and magnetic resonance imaging of the pancreas. Further evaluation was done with endoscopy which revealed a retained stone extraction basket from a previous endoscopic retrograde pancreatography resulting in recurrent episodes of acute on chronic pancreatitis. Despite the retained foreign body being removed, he subsequently developed further complications of portal vein thrombosis as a result of the recurrent acute on chronic pancreatitis that required anticoagulation. Conclusion This case highlights the importance of retrieving any foreign body from the pancreas, especially at the head, to prevent future complications from developing.